Phosphorylation of Arl4A/D promotes their binding by the HYPK chaperone for their stable recruitment to the plasma membrane - Lin, Ming-Chieh; Yu, Chia-Jung; Lee, Fang-Jen S. (Proceedings of the National Academy of Sciences - PNAS, 2022)
The Arl4 small GTPases participate in a variety of cellular events, including cytoskeleton remodeling, vesicle trafficking, cell migration, and neuronal development. Whereas small GTPases are typically regulated by their GTPase cycle, Arl4 proteins have been found to act independent of this canonical regulatory mechanism. Here, we show that Arl4A and Arl4D (Arl4A/D) are unstable due to proteasomal degradation, but stimulation of cells by fibronectin (FN) inhibits this degradation to promote Arl4A/D stability. Proteomic analysis reveals that FN stimulation induces phosphorylation at S143 of Arl4A and at S144 of Arl4D. We identify Pak1 as the responsible kinase for these phosphorylations. Moreover, these phosphorylations promote the chaperone protein HYPK to bind Arl4A/D, which stabilizes their recruitment to the plasma membrane to promote cell migration. These findings not only advance a major mechanistic understanding of how Arl4 proteins act in cell migration but also achieve a fundamental understanding of how these small GTPases are modulated by revealing that protein stability, rather than the GTPase cycle, acts as a key regulatory mechanism.